Faktor-Faktor Yang Mempengaruhi Kelengkapan Imunisasi Dasar Pada Bayi Di Posyandu Dewi Sartika Kota Malang - Maemunah, Neni; Susmini, Susmini; Tuanany, Nona N (Universitas Tribhuwana Tunggadewi, 2023)
The reasons behind most of the mothers' refusal to fully immunize their children include a lack of understanding about the immunization process, including an ignorance of the recommended vaccination schedule, the value of immunization, the best time to immunize, and fear of adverse reactions. The study's purpose was to understand the factors that affect the basic vaccination of babies in Posyandu Dewi Sartika Kota Malang. This research is quantitative, with the research design being cross-sectional. The population of 40 mothers who have babies aged 0–12 months in Posyandu Dewi Sartika Kota Malang in 2021. Samples of 40 were recruited using total sampling techniques. The questionnaires were used to collect information about the mother's occupations, knowledge, attitudes, education, experience, health, and age. Data were analyzed using a multiple linear regression test (significance value of p 0,05). The results showed that the mother’s occupation (p = 0,031), knowledge (p = 0,005), attitude (p = 0,027), education (p = 0.031), experience (p = 0,022), health information, and age (p = 0,019) simultaneously influenced the completeness of basic immunization. The most dominant factor was the knowledge factor (p = 0,005). Further research to explore the effect of cultural factors and motivations of mothers when providing fully basic vaccinations to babies is expected.